The importance of family communication in mitigating parent-child verbal violence in Jakarta - Ayuningtyas, Fitria; Ali, Anuar; Hayati, Kumala; Venus, Anter; Zahwa, Aulia Putri; Didavieny, Keysha (Faculty of Communications Science, Dr. Soetomo University, 2025)
Children in homes are particularly susceptible to experiencing violence, especially verbal violence. Violence against children in Jakarta is a common occurrence and a significant concern in Jakarta's urban society. Specifically, verbal violence affects children by impairing their psychological development and obstructing their self-growth. This research examined the significance of family communication in mitigating verbal violence between parents and children in Jakarta through a qualitative methodology with a phenomenology approach. Data was gathered by observation and comprehensive interviews with five informants residing near Jakarta, subsequently transcribed and analysed utilising NVIVO 12. Additionally, the researcher performed a literature analysis by examining prior studies concerning the impact of family communication on reducing parent-child verbal violence. The research results indicate that the function of family communication is contingent upon the awareness of adults, particularly parents, who play a significant role in implementing family communication patterns. This includes providing appropriate examples of emotional expression and actively inquiring about their children's daily experiences. Verbal violence in children can be mitigated by effective family communication.